Antimicrobial, Cytotoxic, and Antioxidant Potential of a Novel Flavone "6, 7, 4′-Trimethyl Flavone" Isolated from Wulfenia amherstiana. (24th February 2020) - Kakar, Maria; Amin, Muhammad Usman; Alghamdi, Saad; Sahibzada, Muhammad Umar Khayam; Ahmad, Nisar; Ullah, Naseem
Abstract : Wulfenia amherstiana belongs to the Scrophulariaceae family and various plants of this family are known for their biological activities. The present study was focused on the isolation of bioactive compounds including a novel flavone 6, 7, 4′-trimethyl flavone (TMF) along with three known flavonoids such as quercetin, rutin, and a steroid β -sitosterol which were isolated from the ethanolic extract of W. amherstiana (Himalayan Wulfenia) through column chromatography and purified by using HPLC. Their structures were identified and elucidated through electron ionization mass spectroscopy (EIMS), 1DNMR ( 1 H-NMR and 13 C-NMR), and 2DNMR (COSY, HMQC, and HMBC) spectroscopy. The antimicrobial activities of this novel compound were evaluated through agar well diffusion method, while antioxidant and cytotoxic activities were assessed through 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free-radical scavenging assay and brine shrimp lethality assay, respectively. The NMR data revealed that TMF is a novel compound. TMF showed potential antibacterial and antifungal activities against Staphylococcus aureus (MIC = 128 μ g/ml) and Candida albicans (MIC = 128 μ g/ml). The cytotoxic potential of TMF was determined from brine shrimp lethality assay with LD50 of 127.01 μ g/ml. The free-radical scavenging potential of TMF at various concentrations implicated its strong antioxidant activity in vitro. The results revealed that TMF demonstrated substantial antimicrobial activity against S. aureus and C. albicans, strong antioxidant activity, and moderately cytotoxic activity.